The role of health in education and human capital: Why an integrated approach to school health could make a difference in the futures of schoolchildren in low-income countries - Cohee, Lauren M.; Halliday, Katherine E.; Gelli, Aulo; Mwenyango, Irene; Lavadenz, Fernando (American Society of Tropical Medicine and Hygiene, 2020)
Healthy students learn better, yet most current investments in schoolchildren focus on education and learning while largely neglecting the health of the learner. Some school-based interventions, such as school feeding and deworming, are already successfully targeted at this age-group, but the efficiency and cost-effectiveness of such programs could be greatly enhanced by better integrated delivery alongside other priority health interventions. A symposium at the society’s 68th annual meeting launched a process to explore how integrated delivery of school-based interventions can address prevalent health conditions in school-age children.